Efektivitas Pembelajaran Physics Edutainment dengan Bantuan Media PhET terhadap Kemampuan Berfikir Logis Peserta Didik - ananda, mia dwi; sari, milya; Roza, Media (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to determine the effectiveness of Physics Edutainment learning with PhET media on the logical thinking ability of Payakumbuh 2 Senior High School students. This type of research is a quasi experiment using Counterbalance Design. The research population is class XI MIPA with sample classes XI MIPA 5 and XI MIPA 7. The research instruments used was a tests. Data were analyzed using Two-Sample Assuming Equal Variances. The research results in terms of knowledge aspects, the average score of students' logical thinking ability tests was better with Physics Edutainment learning. Mastery learning outcomes reach 90.7% and the average value of the KKM is 88. Then it can be concluded that the learning of Physics Edutainment is effective in improving students' logical thingking ability in the matter of wave interference and global warming symptoms.Â Â